Faktor sosial, ekonomi, dan pemanfaatan posyandu dengan kejadian stunting balita keluarga miskin penerima PKH di Palembang - Nur Farida Rahmawati; Nur Alam Fajar; Haerawati Idris (Jurnal Gizi Klinik Indonesia, 2020)
Social, economic factors, and utilization of posyandu towards stunting among toddlers of poor families of PKH recipients in PalembangBackground: Stunting is a nutritional problem caused by chronic malnutrition. Stunting can result in decreased concentration, memory damage, decreased learning, and school performance, decreased cognitive function, impaired motor development, and has a long-term impact on reducing productivity, thus inhibiting economic growth and causing intergenerational poverty. Stunting can be influenced by social, economic, and access to health services factors. Objective: To analyze the correlation of social, economic, and utilization of integrated services post (pos pelayanan terpadu/posyandu) with the incidence of stunting of under-fives in poor families in Palembang. Methods: This study used a quantitative method with a cross-sectional design in March-April 2019. The population was toddlers aged 24-59 months from poor families in Palembang, with the criteria receiving the cash transfer program from the Indonesian Government, called Program Keluarga Harapan (PKH). Samples were 100 people were chosen by proportional sampling. Data were analyzed by using the Chi-Square test and regression logistic test. Results: The proportion of stunting among toddlers in poor families of PKH recipients in Palembang was 29%. Multiple logistic regression test shows 4 (four) independent variables have a significant correlation to the incidence of stunting simultaneously. Those variable are maternal education (p=0.003, OR=7.278, 95% CI: 1.928-27.474), birth order (p=0.013, OR=0.144, 95% CI: 0.031-0.664), number of family members (p=0.013, OR=10.809, 95% CI:  1.639-71.278),irregular utilization of Posyandu (p=0.041, OR=3.524, 95% CI:1.055-11.768), and never using Posyandu (p=0.019, OR=5.282, 95% CI: 1.313-21.239). Low maternal education, huge family members (more than 4), irregularly and never use Posyandu increase risk of stunting 7.2 times, 10.8 times, 3.5, and 5.2 times, otherwise first or second birth order was a protective factor of stunting. Conclusions: Maternal education and utilization of Posyandu are protective factors, meanwhile huge family members (more than 4) and third or more birth order can increase stunting incidence among toddlers of poor families of PKH recipients.